Updated list and new records of macroalgae from the Gulf of Morrosquillo, Colombian Caribbean - Quintana Manotas, Humberto Luis; Hernández-Contreras, Diego Alexander; Gavio, Brigitte (Instituto de Ecología, A.C., 2024)
Background and Aims: Macroalgae are primary producers of marine ecosystems, so the information regarding their species composition and distribution is necessary to develop conservation strategies and sustainable use of the coastal coastlines they inhabit. However, in different marine regions of Colombia, such as the Gulf of Morrosquillo, this knowledge is scarce, requiring a greater sampling effort and constant updating of data. Therefore, this work aims to provide an updated list of the macroalgae in the aforementioned region, based on published and unpublished biological records and recent sampling. Methods: Bibliographic information was compiled from historical records from 1976 to the present and complemented with sampling in one location in the Gulf of Morrosquillo. The taxa were organized and updated based on the most recent nomenclature, and the geographical affinity of the algal flora was determined using the Cheney index.Key results: The occurrence of 97 taxa classified in three classes, 15 orders, 32 families and 54 genera. Red algae, with 48 taxa, were the group that contributed the largest number of species, and the phycoflora of the region was of a mixed type according to the Cheney index. Six new annotated and illustrated records were reported for the Gulf: Antithamnionella breviramosa, Centroceras gasparrinii, Bostrychia tenella, Melanothamnus sphaerocarpus, Agardhiella ramosissima and Feldmannia mitchelliae.Conclusions: The inventory of macroalgae in the evaluated region was updated, showing a clearer historical panorama of the sampled areas, which suggests an extraordinary potential in the future discovery of new records that would increase the knowledge about the phycoflora of the Colombian Caribbean, particularly because the records of encrusting red algae, epiphytic and epizoic species are non-existent.